Characterization and water vapor sorption property of ABA‐type triblock copolymers derived from polyimide and poly(methyl methacrylate). Issue 3 (14th May 2013) - Kanehashi, Shinji; Koyama, Yusuke; Ando, Shota; Konishi, Shimpei; Shindo, Ryohei; Miyata, Sou; Sato, Shuichi; Miyakoshi, Tetsuo; Nagai, Kazukiyo
<x xml:space="preserve">Abstract</x> Different composition of PMMA‐co‐6FDA‐TeMPD‐co‐PMMA ABA‐type triblock copolymers were synthesized by ATRP. The linear correlation is observed between the water vapor solubility and the polymer molecular polarity in triblock copolymers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>